Using AI in English Language Learning: Perspectives of Indonesian EFL Learners - Amrina Rosyada; Lita Liviani Taopan (Salus Cultura, 2025)
The world of rapid and advanced technology has pushed every aspect of life to transform and keep up with the era, including the transformation of education. The transformation of education that is currently unstoppable is the use of Artificial Intelligence (AI) in the world of education. This study aims to learn more about the use of AI in English Language Learning (ELL) based on the perspective of English as a Foreign Language (EFL) students in Indonesia. Involving 29 EFL students from two private universities in Jakarta and East Nusa Tenggara, this study conducted a qualitative case study research approach. Data in this study were collected using a set of questionnaires with eight open-ended questions given to EFL students online through the Google Form application. The results showed that all EFL students in Jakarta and East Nusa Tenggara were familiar with AI and used it in the ELL process. The learners have various perspectives on AI’s benefits and obstacles. This study has provided insight into the perspective of EFL students in using advanced technology, especially AI, as a medium or tool to support the English Language Learning (ELL) process in Indonesia.